Isolation of strawberry anthocyanins using high-speed counter-current chromatography and the copigmentation with catechin or epicatechin by high pressure processing. (1st May 2018) - Zou, Hui; Ma, Yan; Xu, Zhenzhen; Liao, Xiaojun; Chen, Ailiang; Yang, Shuming
Highlights: Pelargonidin-3-rutinoside, cyanidin-3-glucoside and pelargonidin-3-glucoside were isolated by high-speed counter-current chromatography. The absorbance of epicatechin/pelargonidin-3-glucoside and catechin/pelargonidin-3-glucoside solution at pH 3.6 with molar ratio of 50:1 and 10:1 was significantly increased by high pressure. Abstract: Three anthocyanins were isolated from strawberry extract by high-speed counter-current chromatography, using a biphasic mixture of tert -butyl methyl ether, n -butanol, acetonitrile, water and trifluoroacetic acid (2.5:2.0:2.5:5.0:1.0%). The anthocyanins were identified as pelargonidin-3-rutinoside, cyanidin-3-glucoside and pelargonidin-3-glucoside with purity of 95.6%, 96.2% and 99.3% respectively. Additionally, the copigmentation reaction rates between pelargonidin-3-glucoside and phenolic acids (catechin or epicatechin) at pH 1.5 and 3.6, pressure 0.1 and 500 MPa, and temperature 60 °C were calculated. The absorbance of pelargonidin-3-glucoside at pH 3.6, with high quantity of phenolic acids was significantly increased by high pressure. The complex of pelargonidin-3-glucoside/catechin has a binding energy of 78.64 kJ/mol at pH 3.6, and 39.13 kJ/mol at pH 1.5; pelargonidin-3-glucoside/epicatechin has a binding energy of 75.34 kJ/mol at pH 1.5 and 54.47 kJ/mol at pH 3.6. The hydrogen bond and van der Waals interaction were the main forces contributing to the structures of complex.